Does one of the two most commonly used scoring systems have a decisive advantage over the other in diagnosing acute appendicitis in pregnant women?. Issue 17 (28th April 2023) - Bardakçi, Osman; Bahçecioğlu, İbrahim Burak and Tatli, Faik and Özgönül, Abdullah and Güldür, Muhammet Emin and Uzunköy, Ali
Abstract : This study aimed to compare the accuracy and reliability of Alvarado Score (AS) and Appendicitis Inflammatory Response Score (AIRS) in pregnant women undergoing surgery for acute appendicitis (AA). The files of 53 pregnant women with a diagnosis of AA who underwent surgery in our clinic between February 2014 and December 2018 were examined retrospectively. The patients were divided into 3 groups as follows: first trimester between 0 and 14 weeks, second trimester between 15 and 28 weeks, and third trimester between 29 and 42 weeks. The AS and AIRS values were calculated according to preoperative physical examination and laboratory results. The mean age of the patients was 28.58 (18–44) years. According to the pathology results, appendicitis was detected in 16 of 23 patients in the first trimester, in 22 of 25 patients in the second trimester, and in 2 of 5 patients in the third trimester. The AIRS was ≥ 9 in 9 patients and the AS was ≥ 7 in 19 of the 23 patients in the 1st trimester, while the AIRS was ≥ 9 in 11 patients and the AS was ≥ 7 in 19 of the 25 patients in the 2nd trimester. However, in the 3rd trimester, the AIRS was ≥ 9 in 2 patients and AS was ≥ 7 in 4 of the 5 patients. In conclusion, when the data obtained from the present study were evaluated, it was determined that both AS and AIRS are effective methods for diagnosing AA in pregnant women.